Cardiovascular Toxicity of Carfilzomib: The Real-World Evidence Based on the Adverse Event Reporting System Database of the FDA, the United States - Zhai, Yinghong; Ye, Xiaofei; Hu, Fangyuan; Xu, Jinfang; Guo, Xiaojing; Cao, Yang; Lin, Zhen; Zhou, Xiang; Guo, Zhijian; He, Jia (Frontiers in Cardiovascular Medicine, 2021)
Background: Carfilzomib, an effective proteasome inhibitor agent for the therapy of relapsed and refractory multiple myeloma, has been related to a significant number of cardiovascular events. However, patterns of cardiovascular complications associated with this agent remain poorly characterized in real-world settings. Objective: To gain further insight into the frequency, spectrum, clinical features, timing, and outcomes of carfilzomib-related cardiovascular toxicities. Methods: This disproportionality (case/non-case) study was conducted leveraging records from FAERS database from 2014 to 2019. Cardiovascular events were defined and broadly categorized eight entities using narrow version of the Standardized MedDRA Queries (SMQs). Reporting odds ratios (ROR) and information component (IC) were calculated to measure disproportionality. Additionally, statistical shrinkage was applied to reduce false-positive signals. Results: The final number of records involved was 28479963, with 3370 records submitted for carfilzomib related cardiovascular events. Significant disproportionality association between carfilzomib administration and cardiovascular events was captured (IC025/ROR025=0.85/1.95) when exploring in the entire database. Upon further analysis, all eight broad categories of cardiovascular toxicities were disproportionately associated with carfilzomib with varying frequencies, time-to-onset, and severities. Cardiomyopathy-related complications (N=1301, 38.61%), embolic and thrombotic events (N=821, 24.36%), and cardiac failure (N=765, 22.70%) largely comprised the reported problems. Notably, the strongest signal was detected for cardiac failure (IC025/ROR025=1.33/2.59), followed by pulmonary hypertension (IC025/ROR025=1.19/2.34). Median onset time of cardiovascular events was 41days (Q1-Q3: 9-114 days), with the shortest median time being 16 days (Q1-Q3: 4-85 days) for ischemic heart disease, with the longest time being 68 days (Q1-Q3: 21-139 days) for embolic and thrombotic events. Torsade de pointes/QT prolongation was identified as a new complication (IC025/ ROR025=0.33/1.29) and was particularly noteworthy for highest death proportion (44.11%). Conclusions: Treatment with carfilzomib can lead to severe and versatile cardiovascular events. Early and intensive monitoring is important, particularly in the first 3 months after carfilzomib initiation. Maximizing the beneﬁt while reducing potential cardiovascular harms of carfilzomib should become a priority.